Research Opportunities in Stroke Prevention for Atrial Fibrillation: A Report From a National Heart, Lung, and Blood Institute Virtual Workshop. Issue 3 (28th February 2023) - Go, Alan S.; Al-Khatib, Sana M.; Desvigne-Nickens, Patrice; Bansal, Nisha; Bushnell, Cheryl D.; Fang, Margaret C.; Freeman, James V.; Gage, Brian F.; Hanke, Thorsten; Hylek, Elaine M.; Lopes, Renato D.; Noseworthy, Peter A.; et al.
Abstract : Atrial fibrillation (AF) is one of the strongest risk factors for ischemic stroke, which is a leading cause of disability and death. Given the aging population, increasing prevalence of AF risk factors, and improved survival in those with cardiovascular disease, the number of individuals affected by AF will continue increasing over time. While multiple proven stroke prevention therapies exist, important questions remain about the optimal approach to stroke prevention at the population and individual patient levels. Our report summarizes the National Heart, Lung, and Blood Institute virtual workshop focused on identifying key research opportunities related to stroke prevention in AF. The workshop reviewed major knowledge gaps and identified targeted research opportunities to advance stroke prevention in AF in the following areas: (1) improving risk stratification tools for stroke and intracranial hemorrhage; (2) addressing challenges with oral anticoagulants; and (3) delineating the optimal roles of percutaneous left atrial appendage occlusion and surgical left atrial appendage closure/excision. This report aims to promote innovative, impactful research that will lead to more personalized, effective use of stroke prevention strategies in people with AF.